Hubungan Antara Picky Eating dengan Status Gizi pada Anak Usia Prasekolah di Ra. Al-Hidayah Kota Surabaya - Hanifah Niken Ardilah; Lini Anisfatus Sholihah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Preschool children are those aged between 3-6 years. Eating behavior disorders that occur in children, such as picky eating, significantly impact their nutritional status, which is related to their growth and development. One of the eating problems in children, particularly in preschoolers, is picky eating, which affects their nutritional status. This study aims to determine the relationship between picky eating and nutritional status in preschool children at RA. Al-Hidayah in Surabaya. This research is quantitative with a cross-sectional approach. The respondents of this study were 40 children. Data collection techniques included self-administered questionnaires and measurements of height and weight. The instruments used were questionnaires, digital scales, and microtoise. Data analysis in this study used the Spearman rank correlation test with proportional random sampling. The results showed that 58% of subjects experienced picky eating. Most of the subjects in this study had normal weight, normal height, and good nutritional status. The analysis results indicated a significant relationship between picky eating and nutritional status based on weight-for-age (p-value = 0.019). However, there was no significant relationship between picky eating and nutritional status based on height-for-age (p-value = 0.619) and weight-for-height (p-value = 0.176). In overcoming the problem of picky eating, it is recommended for agencies to provide education or nutritional counseling to parents and caregivers so that they can implement appropriate parenting styles and pay attention to children's nutritional needs properly.